Neurobrucellosis presenting with the features of meningoencephalitis: A case report from Nepal. (August 2022) - Acharya, Aakash; Regmi, Anil; Manandhar, Kabita; Yaday, Jayant; Karki, Pragya
Abstract: Introduction and importance: Brucellosis or Malta fever is a zoonotic disease caused by the Brucella species. Patients with neurobrucellosis may present with features of meningoencephalitis. Thus, a high degree of suspicion is required for the diagnosis in the endemic region. Case presentation: A 13-year old female with a history of exposure to domestic animals presented with the features of meningoencephalitis (intermittent fever with chills and rigor and generalized tonic-clonic seizure). Clinical findings and investigations: Examination revealed drowsy and lethargic patient with bilateral edema up to mid-shin. Neck rigidity was present. Lab findings include leukocytosis with neutrophilic and erythrocyte sedimentation rate (25 mm/hr). CECT of the brain revealed vasogenic edema. Routine CSF examination was insignificant for common bacterial, viral, fungal or tubercular etiology. CSF ELISA confirmed the presence of Brucella antibody. Conclusion: When patients present with undulant fever, lethargy, seizure, or other features of meningitis/encephalitis, the diagnosis of neurobrucellosis must be considered after common pathological causes are ruled out. Highlights: Brucellosis or Malta fever is a zoonotic disease caused by the Brucella species. Patients with Neurobrucellosis may present with features of meningoencephalitis. A high degree of suspicion is required for the diagnosis in the endemic region. Patients with undulant fever, seizure, or other features of meningoencephalitis should be tested for Neurobrucellosis.